2005
DOI: 10.1063/1.1944719
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis wavelength dependence of the translational anisotropy and the angular momentum polarization of O2(aΔg1) formed from the UV photodissociation of O3

Abstract: The translational anisotropy and angular momentum polarization of the O(2)(a (1)Delta(g),v = 0;J = 15-27) molecular photofragment produced from the UV photodissociation of O(3) in the range from 270 to 300 nm have been determined using resonance-enhanced multiphoton ionization in conjunction with time-of-flight mass spectrometry. At the shortest photolysis wavelengths used, the fragments exhibit the anisotropic vector correlations expected from a prompt dissociation via the (1)B(2) <--(1)A(1) transition. Devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…Hancock et al were the first to report even-odd alternations in O 2 (a 1 Δ g ) photofragment vector correlations, and found that following the 270-nm photolysis of ozone at 140 K, the μ-j and v-j angles were smaller for the odd fragments than for the even fragments (7). Similar results have been reported for the photolysis of 140 K ozone at multiple wavelengths (8,13,15), and for the 266-nm photolysis of ozone at 70, 115, and 170 K (33). One explanation for the observed alternation is differences in the formation of the A′ and A′′ Λ-doublets.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Hancock et al were the first to report even-odd alternations in O 2 (a 1 Δ g ) photofragment vector correlations, and found that following the 270-nm photolysis of ozone at 140 K, the μ-j and v-j angles were smaller for the odd fragments than for the even fragments (7). Similar results have been reported for the photolysis of 140 K ozone at multiple wavelengths (8,13,15), and for the 266-nm photolysis of ozone at 70, 115, and 170 K (33). One explanation for the observed alternation is differences in the formation of the A′ and A′′ Λ-doublets.…”
Section: Resultssupporting
confidence: 53%
“…In addition to the rotational population alternation, even-odd alternations in the vector correlations of the O 2 (a 1 Δ g ) fragments have been previously measured (7,8,13,15). Vector correlations describe the average angles between the transition dipole moment (μ), fragment recoil velocity vector (v), and fragment angular momentum vector (j), and can provide a window into photodissociation dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…translational anisotropy and angular momentum alignment) yield additional and more detailed information about the fragmentation dynamics. [111][112][113][114] Of course, the calculation of such quantities is much more demanding, but still tractable with our present day knowledge of the PESs involved. In order to understand the unusual isotopic fractionation of ozone in the atmosphere 115 isotopic effects in photodissociation are important.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been realized that the ozone cation and anion deserve attention since the ozone neutral, positive, and negative chemistry could affect each other in unanticipated ways [3]. In comparison with the vast literature on neutral ozone, not least its photochemical properties (see, e.g., [4,5]), work on the ozone cation is sparse [6], but definitely needed for an understanding of the O 3 ion chemistry in the stratosphere and lower ionosphere. It is worth noting that ozone has also been detected in the polar regions of Mars [7] and on the Jovian satellite Ganymede [8].…”
mentioning
confidence: 99%